Solvent and pH-stable poly(2,5-benzimidazole) (ABPBI) based UF membranes: preparation and characterizations - Lohokare, Harshada R.; Chaudhari, Harshal D.; Kharul, Ulhas. K. (Journal of Membrane Science, 2018)
Poly(2,5-benzimidazole), commonly known as ABPBI, is an excellent thermo-chemically stable polymer that is widely evaluated as a proton exchange membrane material in a fuel cell. Its niche intrinsic characteristics could be highly useful in the membrane preparation for various separation applications, especially under harsher environments. To gain insights towards this feasibility, ABPBI based supported membranes were prepared by phase inversion method. Effects of the nonwoven porous support material (polypropylene/polyester), non-solvent (water/0.5 N NaOH) and polymer concentration (6 or 4 wt%) on the membrane properties (water flux, rejection and porosity) were investigated. The stability of these membranes towards common organic solvents, concentrated acid (25 N H2SO4), base (2.5 N NaOH) and an autoclave condition was analyzed. ABPBI membrane showed a pore collapse after drying. In order to avoid this, the glycerol treatment was not only found to be suitable but also repeatable, without significant deviations in the water flux.
Keywords: ABPBI membrane; Pore size distribution; Solvent stable membranes; Ultrafiltration